To compare the functions \( f(x) = \sqrt{2x} \) and \( g(x) = \sqrt{2x} + 3 \), let's analyze each statement one by one.
-
The graphs have different domains.
- Both functions \( f(x) = \sqrt{2x} \) and \( g(x) = \sqrt{2x} + 3 \) only exist for \( x \geq 0 \) since the square root function is only defined for non-negative numbers. Thus, their domains are the same: \( [0, \infty) \). This statement is false.
-
Both graphs go through (−1,−1), (0,0), and (1,1).
- For \( f(x) = \sqrt{2x} \):
- At \( x=0 \): \( f(0) = \sqrt{2(0)} = 0 \) (so, it goes through (0, 0)).
- At \( x=1 \): \( f(1) = \sqrt{2(1)} = \sqrt{2} \), approximately 1.414 (so, it does not go through (1, 1)).
- At \( x=-1 \): \( f(-1) \) is not defined (so, it does not go through (-1, -1)).
- For \( g(x) = \sqrt{2x} + 3 \):
- At \( x=0 \): \( g(0) = \sqrt{2(0)} + 3 = 3 \).
- At \( x=1 \): \( g(1) = \sqrt{2(1)} + 3 = \sqrt{2} + 3 \), approximately 4.414 (not (1, 1)).
- At \( x=-1 \): \( g(-1) \) is also not defined.
- Thus, this statement is false.
- For \( f(x) = \sqrt{2x} \):
-
They are both decreasing on their domains.
- For \( f(x) = \sqrt{2x} \) and \( g(x) = \sqrt{2x} + 3 \), both functions are increasing as \( x \) increases. Therefore, this statement is false.
-
When \( x>1 \), the function \( g(x) = \sqrt{2x} + 3 \) is greater than \( f(x) = \sqrt{2x} \).
- For \( x > 1 \):
- Since \( g(x) = \sqrt{2x} + 3 \) adds a constant (3) to \( f(x) \), it is clear that \( g(x) \) is always greater than \( f(x) \) for \( x > 1 \). This statement is true.
- For \( x > 1 \):
Based on the evaluations, the correct answer is:
When x>1, the function g(x)=√(2x)+3 is greater than f(x)=√(2x).